Targeted RNA-Based Oxford Nanopore Sequencing for Typing 12 Classical HLA Genes - Johansson, Tiira; Koskela, Satu; Yohannes, Dawit A.; Partanen, Jukka; Saavalainen, Päivi (Frontiers in Genetics, 2021)
Identification of Human Leukocyte Antigen (HLA) alleles from next-generation sequencing (NGS) data is challenging because of the high polymorphism and mosaic nature of HLA genes. Owing to the complex nature of HLA genes and consequent challenges in allele assignment, Oxford Nanopore Techologies’ (ONT) single-molecule sequencing technology has been of great interest due to its fitness for sequencing long reads. Here, we describe a targeted RNA-based method for HLA typing using ONT sequencing and SeqNext-HLA SeqPilot software (JSI Medical Systems GmbH). 12 classical HLA genes were enriched from cDNA of 50 individuals, barcoded, pooled, and sequenced in ten MinION R9.4 SpotON flow cell runs producing over 30 000 reads per sample. Using barcoded 2D reads, SeqPilot assigned HLA alleles to two-field typing resolution or higher with the average read depth of 1750x. Sequence analysis resulted in 99–100% accuracy at low-resolution level (one-field) and in 74–100% accuracy at high-resolution level (two-field) with the expected alleles. There are still some limitations with ONT RNA sequencing, which interfere confident allele assignment. These issues need to be inspected carefully in the future to improve the allele call rates. Nevertheless, here we show that sequencing of multiplexed cDNA amplicon libraries on ONT MinION can produce accurate high-resolution typing results of 12 classical HLA loci. For HLA research, ONT RNA sequencing is a promising method due to its capability to sequence full-length HLA transcripts. In addition to HLA genotyping, the technique could be also be applied for simultaneous expression analysis.